DEIXIS IN BULLET TRAIN MOVIE (2022) - Dimas Wahyu Erdianto; Adip Arifin (IKIP Siliwangi, 2024)
This study aims to identify the deixis spoken by Ladybug, the main character of Bullet Train. This research used descriptive qualitative method with content analysis to collect the data. The researchers apply the Levinson’s theory on deixis type to classify the findings. The data were collected through the following stages: 1) watch the movie, 2) download the movie script, 3) collect the utterance spoken by Ladybug character that contains deixis, 4) classify the data into types based on Levinson’s theory, and 5) drawing conclusion based on the analysis. The result of this research showed that there were 182 data that identified as deixis. The data consisted of five types of deixis: personal, spatial, temporal, social, and discourse deixis. Personal deixis is the most dominant deixis used in the movie Bullet Train by 159 out of 179 data. Five types of deixis found in Ladybug’s utterances from the Bullet Train movie were person, place, time, social, and discourse deixis. In this research the amount of deixis is 179 words consisting of person deixis, place deixis, time deixis, social deixis, and discourse deixis. The most used deixis by the Ladybug character is person deixis 89% of total deixis spoken. Furthermore the less used deixis are place deixis 8%, time deixis 1%, social deixis 1%, and discourse deixis 1%. Therefore, this research is expected to be the additional reference for understanding the use and function of deixis in real communication.